Transcriptional Regulation of Grass Secondary Cell Wall Biosynthesis: Playing Catch-Up with Arabidopsis thaliana - Handakumbura, Pubudu P.; Hazen, Samuel P. (Frontiers in Plant Science, 2012)
Secondary cell wall synthesis occurs in specialized cell types following completion of cell enlargement. By virtue of mechanical strength provided by a wall thickened with cellulose, hemicelluloses, and lignin, these cells can function as water-conducting vessels and provide structural support. Several transcription factor families regulate genes encoding wall synthesis enzymes. Certain NAC and MYB proteins directly bind to the SNBE and AC elements upstream of structural genes and other transcription factors. The most detailed model of this regulatory network is established predominantly for a eudicot, Arabidopsis thaliana. In grasses, both the patterning and the composition of the secondary cell walls is distinct from that of eudicots, differences that suggest regulation is likewise distinct. Putative rice and maize orthologs of several eudicot cell wall regulators genetically complement mutants of A. thaliana or result in wall defects when constitutively overexpressed; nevertheless, aside from a maize, ZmMYB31, and a switchgrass protein, PvMYB4, function has not been tested in a grass. Similar to the seminal work conducted in A. thaliana, gene expression profiling in maize, rice, and other grasses implicates additional genes as regulators. Characterization of these genes will continue to elucidate the relationship between the transcription regulatory networks of eudicots and grasses.